Aluminum / titanium alloy gradient structure laser additive manufacturing method
By using TiNbV or TiNbVZr high-entropy alloy as transition layer in the aluminum/titanium gradient structure, the problems of cracking and low bonding strength of the aluminum/titanium gradient structure are solved, and high-performance aluminum/titanium alloy gradient structure manufacturing is achieved, reducing the Production costs and provides new methods for other heterogeneous metal connections.
Patent Information
- Application Number
- CN202411362510.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Aluminum/titanium gradient structural materials have problems of interfacial cracking and low binding strength in laser additive manufacturing, which is mainly due to the residual stress and intermetallic compound formation caused by differences in physical and chemical properties of titanium and aluminum, making it difficult for traditional methods to form efficiently.
TiNbV or TiNbVZr high-entropy alloy is used as the intermediate transition layer. A high-entropy alloy transition layer is prepared on the surface of the titanium alloy through laser additive manufacturing technology, and an aluminum alloy layer is prepared on its surface. The solid solution characteristics of the high-entropy alloy are used to reduce titanium and aluminum. The diffusion rate of the brittle intermetallic compounds is inhibited and defect-free connection is achieved.
Significantly improve the bonding strength at the aluminum alloy/titanium alloy interface, avoid defects caused by direct contact, shorten the R&D cycle, reduce production costs, meet the needs of integrated manufacturing of high-performance heterogeneous metals, and connect other heterogeneous metals. Provides new preparation ideas.
Smart Images

Figure CN119237745A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser additive manufacturing, and specifically relates to a laser additive manufacturing method for an aluminum / titanium alloy gradient structure. Background Art
[0002] Gradient structure refers to the combination of two or more metal alloys with different chemical compositions and different mechanical properties through a reasonable gradient transition, which is used to meet the service temperature and mechanical property requirements of different parts of the component under the complex service conditions under actual application conditions, and to achieve the effects of reducing costs, reducing weight or improving performance by matching different materials. For example, the aluminum alloy / titanium gradient structure material used in a certain type of wing honeycomb sandwich connects the titanium alloy skin and the internal skeleton of the aluminum alloy together, which can not only reduce the weight of the structure but also improve the overall strength of the structure, ensuring a high vibration resistance limit and stability. The manufacturing principle of point-by-point and layer-by-layer forming of laser additive manufacturing technology also provides a feasible way to prepare aluminum alloy / titanium alloy gradient structures.
[0003] However, the huge differences in physical and chemical properties between titanium and aluminum make it extremely difficult to prepare aluminum / titanium gradient structural materials. In terms of physical properties, titanium and aluminum have huge differences in melting point, density, linear expansion coefficient, etc., which easily produce large residual stress in the bonding area between the two, causing deformation or even cracking; in terms of chemical properties, titanium and aluminum are more active and easily produce intermetallic compounds, which makes it easy for cracks, holes and other defects to appear in the bonding area, seriously reducing the mechanical properties of the interface. Therefore, it is impossible to directly form aluminum alloys and titanium alloys into gradient materials using laser additive manufacturing technology. The current preparation method of aluminum alloy / titanium alloy gradient structures is mainly brazing, but the bonding strength is only about 10-30MPa.
[0004] As a new type of alloy, high entropy alloy breaks through the alloying strategy of using a single element as the main component in the design of traditional alloy materials, and adopts 3-5 kinds of main elements with equal or nearly equal molar ratios to form an alloy system. The concentration of each element in the high entropy alloy is very high, and it has a significant impact on the performance of the high entropy alloy. Due to its high system mixing entropy, it can produce excellent properties different from traditional alloys. With the characteristics of high mixing entropy, slow diffusion rate of hysteretic diffusion and high stability of high entropy alloys, Al and Ti elements tend to form solid solutions without precipitating intermetallic compounds, and at the same time alleviate the difference in physical properties between aluminum alloys and titanium alloys, thus becoming a candidate material for the intermediate transition layer of aluminum alloy / titanium alloy gradient structure. Although there are related reports on high entropy alloys as intermediate transition layers of aluminum alloy / titanium alloy gradient structures, for the simultaneous solid solution of high contents of Al and Ti, further exploration of the high entropy alloy system is still needed to achieve better results. Summary of the invention
[0005] The purpose of the present invention is to provide a laser additive manufacturing method for an aluminum / titanium alloy gradient structure. By combining the optimization of the intermediate transition layer of a high entropy alloy of two preferred components with the laser additive manufacturing technology, a high-performance aluminum / titanium alloy gradient structure is prepared, which can effectively solve the current problems of aluminum / titanium alloy interface cracking and low bonding strength.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for manufacturing an aluminum / titanium alloy gradient structure by laser additive manufacturing, comprising the following steps:
[0008] A high entropy alloy transition layer is prepared on the surface of a titanium alloy using TiNbVZr or TiNbV high entropy alloy powder through a laser additive manufacturing process, and then an aluminum alloy layer is prepared on the surface of the high entropy alloy transition layer through a laser additive manufacturing process.
[0009] Preferably, the atomic ratio of Ti, Nb, V and Zr in the TiNbVZr high entropy alloy powder is 1:0.5-2:0.5-2:0.5-2, and the powder particle size range is 53-250 μm; the atomic ratio of Ti, Nb and V in the TiNbV high entropy alloy powder is 1:0.5-2:0.5-2, and the powder particle size range is 53-250 μm.
[0010] More preferably, the TiNbVZr high entropy alloy powder and the TiNbV high entropy alloy powder are dried at 120° C. for 2 hours before use.
[0011] Preferably, the titanium alloy is pretreated before laser additive manufacturing.
[0012] Preferably, the titanium alloy is an α-type, α+β-type or β-type titanium alloy, and grades include but are not limited to TA2, TC4 or TC11.
[0013] Preferably, the height of the high entropy alloy transition layer is 1-4 mm.
[0014] Preferably, when preparing the high entropy alloy transition layer, the process parameters of the laser additive manufacturing process are: laser beam diameter 3-6 mm, laser power 2-6 KW, scanning speed 500-1500 mm / min, single layer height 0.3-0.6 mm, overlap rate 30-50%, powder feeding rate 800-2000 g / h, and oxygen content less than 80 ppm.
[0015] Preferably, the particle size range of the aluminum alloy powder used in preparing the aluminum alloy layer is 53-250 μm.
[0016] More preferably, the material of the aluminum alloy powder includes but is not limited to aluminum alloys of grades ZL105A, AlSi10Mg, AlSi7Mg or 5A06.
[0017] More preferably, the aluminum alloy powder is dried at 120° C. for 2 hours before use.
[0018] Preferably, when preparing the aluminum alloy layer, the process parameters of the laser additive manufacturing process are: laser beam diameter 3-6 mm, laser power 2-6 KW, scanning speed 500-1500 mm / min, single layer height 0.3-0.6 mm, overlap rate 30-50%, powder feeding rate 500-1000 g / h, and oxygen content less than 80 ppm.
[0019] Preferably, an annealing step is further included after preparing the aluminum alloy layer.
[0020] More preferably, the annealing treatment is carried out at a temperature of 200-500° C., with a holding time of 1-6 hours, and air cooling or furnace cooling.
[0021] The beneficial technical effects of the present invention are as follows:
[0022] The laser additive manufacturing method for an aluminum alloy / titanium alloy gradient structure with an optimized high entropy alloy transition layer of the present invention adopts TiNbV or TiNbVZr high entropy alloy as an intermediate transition layer between aluminum and titanium alloys for the first time, thereby avoiding direct additive contact between the aluminum alloy and the titanium alloy. When TiNbV or TiNbVZr high entropy alloy is used as a transition layer for additive connection between aluminum and titanium alloys, the diffusion rate of titanium atoms and aluminum atoms is reduced, and the solid solubility in the alloy is increased, thereby suppressing the generation of TiAl-based brittle intermetallic compounds and significantly improving the bonding strength at the aluminum alloy / titanium alloy interface.
[0023] Compared with traditional brazing and other methods that are more suitable for connecting regular plates, the present invention uses laser additive manufacturing to prepare aluminum alloy / titanium alloy gradient structures, which can give full play to the characteristics of laser additive manufacturing such as refinement and flexibility, greatly shorten the R&D cycle, reduce production costs, and fully meet the needs of high-performance integrated manufacturing of dissimilar metals.
[0024] The present invention adopts TiNbV or TiNbVZr high entropy alloy as the transition layer for laser additive connection of aluminum and titanium alloys and realizes defect-free connection between the two, which can provide a new preparation idea for the connection of dissimilar metals such as titanium / steel, nickel / steel, titanium / nickel, etc., and can be promoted in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1Schematic diagram of the process of laser additive manufacturing of an optimized aluminum alloy / titanium alloy gradient structure for a high entropy alloy transition layer in an embodiment of the present invention, wherein: 1-laser cladding head; 2-shielding gas input / output joint; 3-powder feeding nozzle; 4-laser beam; 5-laser additive manufacturing of a high entropy alloy transition layer; 6-titanium alloy substrate; 7-laser additive manufacturing equipment workbench; 8-laser additive manufacturing of an aluminum alloy layer.
[0026] Figure 2 The macroscopic actual image and metallographic photograph of the bonding area of the aluminum alloy / titanium alloy gradient structure specimen with optimized TiNbVZr high entropy alloy transition layer prepared in Example 1 of the present invention, wherein A is the macroscopic actual image and B is the metallographic photograph of the bonding area.
[0027] Figure 3 The macroscopic actual image and the metallographic photograph at the bonding area of the aluminum alloy / titanium alloy gradient structure specimen with optimized TiNbV high entropy alloy transition layer prepared in Example 2 of the present invention, wherein A is the macroscopic actual image and B is the metallographic photograph at the bonding area.
[0028] Figure 4 It is a macroscopic physical picture and a metallographic photograph of the bonding area of the aluminum alloy / titanium alloy gradient structure specimen prepared in Comparative Example 1 of the present invention, wherein A is the macroscopic physical picture and B is the metallographic photograph of the bonding area.
[0029] Figure 5 The macroscopic actual image and the metallographic photograph at the bonding area of the aluminum alloy / titanium alloy gradient structure specimen containing the CoCrFeMnNi high entropy alloy transition layer prepared in Comparative Example 2 of the present invention, wherein A is the macroscopic actual image and B is the metallographic photograph at the bonding area.
[0030] Figure 6 The macroscopic physical image and metallographic photograph of the bonding area of the aluminum alloy / titanium alloy gradient structure specimen containing the CoCrFeNi high entropy alloy transition layer prepared in Comparative Example 3 of the present invention, wherein A is the macroscopic physical image and B is the metallographic photograph of the bonding area. DETAILED DESCRIPTION
[0031] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0032] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The schematic diagram of the process of laser additive manufacturing of the aluminum alloy / titanium alloy gradient structure with optimized high entropy alloy transition layer in the embodiment of the present invention is shown in Figure 1 , among which, 1-laser cladding head; 2-shielding gas input / output joint; 3-powder feeding nozzle; 4-laser beam; 5-laser additive manufacturing high entropy alloy transition layer; 6-titanium alloy substrate; 7-laser additive manufacturing equipment workbench; 8-laser additive manufacturing aluminum alloy layer.
[0036] The aluminum alloy / titanium alloy gradient structure test pieces of the embodiment of the present invention and the comparative example are all manufactured by laser additive manufacturing method, using LMD-V type laser forming manufacturing system (part of the structure in the system is shown in FIG. Figure 1 ), the specific operation of the system is: first, the titanium alloy substrate 6 is fixed on the workbench 7 of the laser additive manufacturing system, when the powder feeding nozzle 3 feeds high entropy alloy powder, the laser beam 4 is turned on through the laser cladding head 1, so that the high entropy alloy powder is deposited on the titanium alloy substrate, when the high entropy alloy intermediate transition layer is formed to 1-4mm, the light beam 4 is closed, the powder feeding nozzle 3 feeds aluminum alloy powder, and then the laser beam 4 is turned on to deposit the aluminum alloy part, and the specific forming height can be adjusted according to the use requirements of the component. During the above whole process, inert gas is fed in real time through the protective gas input / output connector 2, and the oxygen content is always kept below 80ppm until the preparation of the gradient structure material is completed (in Example 1, if high entropy alloy powder is not used, the step of feeding high entropy alloy powder can be omitted).
[0037] Example 1
[0038] Laser additive manufacturing of aluminum alloy / titanium alloy gradient structure specimens with optimized TiNbVZr high entropy alloy transition layer:
[0039] S1. Prepare titanium alloy substrate, high entropy alloy and aluminum alloy powder: the titanium alloy substrate is TC11 titanium alloy substrate (nominal chemical composition Ti-6.5Al-3.5Mo-1.5Zr-0.3Si), the outer dimensions are 150mm*120mm*40mm, the high entropy alloy powder composition is TiNbVZr (equiatomic ratio), the particle size is 75-250μm, the aluminum alloy grade is ZL105A (Al-5Si-1Cu-Mg), and the particle size is 75-250μm.
[0040] S2. Treat the titanium alloy substrate, high entropy alloy and aluminum alloy powders: Grind the titanium alloy substrate with sandpaper until the metallic luster is revealed to remove the surface oxide layer, then wipe it with alcohol to remove the surface oil and dry it. The two powders used for molding are dried in a vacuum oven to remove moisture and increase the fluidity of the powder during the molding process. The drying condition is 120℃ for 2h.
[0041] S3. Write the laser additive manufacturing process file and import it into the control system of the equipment: the files for the high entropy alloy transition layer and the additive manufacturing aluminum alloy area are written separately, and the corresponding process parameters are set to facilitate switching and adjustment during the molding process. The process parameters for depositing the high entropy alloy transition layer are: the laser beam diameter is 6mm, the scanning speed is 1000mm / min, the single-layer lifting height is 0.5mm, the laser power is 3.5KW, the powder delivery rate of the powder feeder is 1000g / h, and the overlap rate is 40%. The process parameters for depositing the aluminum alloy area are: the laser beam diameter is 6mm, the scanning speed is 1000mm / min, the single-layer lifting height is 0.5mm, the laser power is 3KW, the powder delivery rate of the powder feeder is 700g / h, and the overlap rate is 40%.
[0042] S4. Fix the prepared titanium alloy substrate on the machine tool workbench, introduce inert gas Ar gas to maintain the oxygen content in the entire molding environment below 80ppm, and adjust the angle of the powder feeding nozzle so that the delivered powder and the laser beam converge at the same point on the substrate.
[0043] S5. Select the process parameter file for forming a high entropy alloy transition layer in the control system, turn on the laser, and form a TiNbVZr high entropy alloy transition layer region on a TC11 titanium alloy substrate with a height of 2 mm.
[0044] S6. Switch the process parameter file of the aluminum alloy forming area in the control system, and form and prepare ZL105A aluminum alloy on the TiNbVZr high entropy alloy transition layer with a height of 20 mm.
[0045] S7. After the preparation is completed and cooled to room temperature, an aluminum alloy / titanium alloy gradient structure with optimized TiNbVZr high entropy alloy transition layer is obtained, and a stress relief annealing heat treatment of 500°C / 6h / AC is performed, and the sample is cooled in the furnace to obtain an aluminum alloy / titanium alloy gradient structure specimen with optimized TiNbVZr high entropy alloy transition layer.
[0046] The macroscopic physical picture of the aluminum alloy / titanium alloy gradient structure specimen with optimized TiNbVZr high entropy alloy transition layer prepared in Example 1 and the metallographic photograph of the bonding area are shown in Figure 2 , where A is the macroscopic picture and B is the metallographic photograph of the bonding area.
[0047] Figure 2 It shows that the aluminum alloy / titanium alloy gradient structure in the specimen has achieved good bonding both at the macro and micro levels, and no defects such as cracks, holes, and unfused components were found.
[0048] Example 2
[0049] Laser additive manufacturing of aluminum alloy / titanium alloy gradient structure specimens with optimized TiNbV high entropy alloy transition layer:
[0050] Compared with Example 1, the only difference is that the equiatomic ratio TiNbV high entropy alloy powder (powder particle size is 75-250μm) is used to replace the equiatomic ratio TiNbVZr high entropy alloy powder to prepare an aluminum alloy / titanium alloy gradient structure specimen with an optimized TiNbV high entropy alloy transition layer.
[0051] The macroscopic physical picture of the aluminum alloy / titanium alloy gradient structure specimen with optimized TiNbV high entropy alloy transition layer prepared in Example 2 and the metallographic photograph of the bonding area are shown in Figure 3 , where A is the macroscopic picture and B is the metallographic photograph of the bonding area.
[0052] Figure 3 It shows that the aluminum alloy / titanium alloy gradient structure in the specimen has achieved good bonding both at the macro and micro levels, and no defects such as cracks, holes, and unfused components were found.
[0053] Comparative Example 1
[0054] Laser additive manufacturing of aluminum alloy / titanium alloy gradient structure specimens:
[0055] Compared with Example 1, the only difference is that the preparation of the high entropy alloy transition layer is omitted, and an aluminum alloy / titanium alloy gradient structure specimen is prepared.
[0056] The macroscopic physical picture of the aluminum alloy / titanium alloy gradient structure specimen prepared in Comparative Example 1 and the metallographic photograph of the bonding area are shown in Figure 4 , where A is the macroscopic picture and B is the metallographic photograph of the bonding area.
[0057] Figure 4 It is shown that due to the huge differences in the physical and chemical properties of aluminum and titanium, there are obvious defects such as cracks and holes in the bonding area.
[0058] Comparative Example 2
[0059] Laser additive manufacturing of aluminum alloy / titanium alloy gradient structure specimens containing CoCrFeMnNi high entropy alloy transition layer:
[0060] Compared with Example 1, the only difference is that the equiatomic ratio of TiNbVZr high entropy alloy powder is replaced by equiatomic ratio CoCrFeMnNi high entropy alloy powder (powder particle size is 75-250μm) to prepare an aluminum alloy / titanium alloy gradient structure specimen containing a CoCrFeMnNi high entropy alloy transition layer.
[0061] Macroscopic physical image of the aluminum alloy / titanium alloy gradient structure specimen containing the CoCrFeMnNi high entropy alloy transition layer prepared in Comparative Example 2 of the present invention and metallographic photograph of the bonding area Figure 5 , where A is the macroscopic picture and B is the metallographic photograph of the bonding area.
[0062] Figure 5 It shows that obvious cracks appear in the bonding area of the high entropy alloy transition layer of the aluminum alloy / titanium alloy gradient structure specimen with the addition of CoCrFeMnNi high entropy alloy transition layer.
[0063] Comparative Example 3
[0064] Laser additive manufacturing of aluminum alloy / titanium alloy gradient structure specimens with CoCrFeNi high entropy alloy transition layer:
[0065] Compared with Example 1, the only difference is that the equiatomic ratio TiNbVZr high entropy alloy powder is replaced by the equiatomic ratio CoCrFeNi high entropy alloy powder (powder particle size is 75-250μm) to prepare an aluminum alloy / titanium alloy gradient structure specimen containing a CoCrFeNi high entropy alloy transition layer.
[0066] The macroscopic physical image of the aluminum alloy / titanium alloy gradient structure specimen containing the CoCrFeNi high entropy alloy transition layer prepared in Comparative Example 3 and the metallographic photograph of the bonding area are shown in Figure 6 , where A is the macroscopic picture and B is the metallographic photograph of the bonding area.
[0067] Figure 6 It shows that obvious cracks appear in the bonding area of the high entropy alloy transition layer of the aluminum alloy / titanium alloy gradient structure specimen with the addition of CoCrFeNi high entropy alloy transition layer.
[0068] Since the specimens prepared in Comparative Examples 1-3 all had obvious cracks in the bonding area, the tensile properties could not be tested.
[0069] The tensile properties of the test pieces prepared in Example 1-2 were tested, and the test results are shown in Table 1.
[0070] Table 1 Tensile properties of aluminum alloy / titanium alloy gradient structure specimens with optimized high entropy alloy transition layer
[0071]
[0072] The results in Table 1 show that the aluminum / titanium gradient structure material prepared by the present invention fully meets the needs of integrated manufacturing of aluminum and titanium dissimilar metals, and provides a new preparation idea for the connection of other high-performance dissimilar metals.
[0073] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for manufacturing aluminum / titanium alloy gradient structure laser additive, characterized in that: The following steps are involved: A high entropy alloy transition layer is prepared on the surface of a titanium alloy using TiNbVZr or TiNbV high entropy alloy powder through a laser additive manufacturing process, and then an aluminum alloy layer is prepared on the surface of the high entropy alloy transition layer through a laser additive manufacturing process.
2. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: The atomic ratio of Ti, Nb, V and Zr in the TiNbVZr high entropy alloy powder is 1:0.5-2:0.5-2:0.5-2, and the powder particle size range is 53-250μm; the atomic ratio of Ti, Nb and V in the TiNbV high entropy alloy powder is 1:0.5-2:0.5-2, and the powder particle size range is 53-250μm.
3. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: The titanium alloy is pretreated before laser additive manufacturing.
4. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: The titanium alloy is an α-type, α+β-type or β-type titanium alloy.
5. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: The height of the high entropy alloy transition layer is 1-4 mm.
6. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: When preparing the high entropy alloy transition layer, the process parameters of the laser additive manufacturing process are: laser beam diameter 3-6 mm, laser power 2-6 KW, scanning speed 500-1500 mm / min, single layer height 0.3-0.6 mm, overlap rate 30-50%, powder feeding rate 800-2000 g / h, and oxygen content less than 80 ppm.
7. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: The particle size range of the aluminum alloy powder when preparing the aluminum alloy layer is 53-250 μm.
8. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: When preparing the aluminum alloy layer, the process parameters of the laser additive manufacturing process are: laser beam diameter 3-6 mm, laser power 2-6 KW, scanning speed 500-1500 mm / min, single layer height 0.3-0.6 mm, overlap rate 30-50%, powder feeding rate 500-1000 g / h, and oxygen content less than 80 ppm.
9. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: After the aluminum alloy layer is prepared, an annealing step is also included.
10. The method for manufacturing aluminum / titanium alloy gradient structure laser additive according to claim 1, characterized in that: The annealing treatment is carried out at a temperature of 200-500° C., with a holding time of 1-6 hours, and is air-cooled or furnace-cooled.
Citation Information
Patent Citations
Laser welding method for dissimilar materials of titanium alloy and aluminum alloy
CN113857669A
Ti / Nb + V composite interlayer for TiAl alloy / steel connection and diffusion welding method
CN115319259A
Titanium / aluminum dissimilar alloy material and preparation method thereof
CN116423941A
Titanium / aluminum composite structure laser additive manufacturing method based on variable-component high-entropy transition layer
CN116809960A
High-entropy fecrcutiv alloy powder for laser melting deposition manufacturing and preparation method therefor
WO2020206724A1
Cited By
Aluminum alloy-titanium alloy component laser additive connection method adopting high-entropy alloy as middle layer
CN119237746A
A method for laser additive joining of aluminum alloy-titanium alloy components using high-entropy alloy as an intermediate layer
CN119237746B
High-temperature-resistant anti-stripping gradient coating as well as preparation method and application thereof
CN121653634A